A Conceptual and Empirical Review of the Structure of Assessment Center Dimensions. (July 2014) - Meriac, John P.; Hoffman, Brian J.; Woehr, David J.
Although the design, scoring, and interpretation of assessment centers (ACs) commonly focuses on job-relevant dimensions, over three decades of past studies have questioned the evidentiary basis underlying dimension-based interpretations of ACs. This review combines multiple approaches to examine the structure of AC dimensions. First, we consulted the AC, job performance, leadership, and personality literatures to articulate competing models of the dimensions underlying AC ratings. Next, meta-analytic confirmatory factor analysis (CFA) was used to compare the fit of these models to existing AC data. The results supported a model including administrative skills, relational skills, and drive. Third, socioanalytic theory was used as a basis to examine the nomological network of these three broad factors, specifically their relationships with general mental ability and the five factor model of personality. The analyses supported the nomological network of drive and administrative skills but less so for relational skills. These findings are discussed with regard to the construct-related validity of AC dimensions, the fidelity of ACs to the broader criterion domain, and the value of applying generalizable models to the analysis of AC ratings.